Proanthocyanidin glycosides from the leaves of Quercus ilex L. (Fagaceae) - Karioti, Anastasia; Bilia, Anna Rita; Gabbiani, Chiara; Messori, Luigi; Skaltsa, Helen (Tetrahedron Letters, 2009)
From the polar extracts of the leaves of Quercus ilex L., two new proanthocyanidin glycosides, namely afzelechin-(4a?8)-catechin-3-O-b-glucopyranoside (1) and afzelechin-(4a?8)-catechin-3-O-a-rhamnopyranoside (2), were isolated in addition to catechin (3), proanthocyanidin B3 (4), prodelphinidin C (5), dehydrodicatechin A (6), quercetin (7) and six known ﬂavonol glucosides with their acylated derivatives (8–13) and ellagic acid (14). The structures of all isolated compounds were established by spectroscopic means, mainly 1D and 2D NMR, as well as LC/MS and HR-MS spectrometric analyses. The absolute con- ﬁguration of compound 1 was determined by CD measurements. The proanthocyanidin glycosides are especially interesting, as they possess the sugar in the upper unit of the dimer, which is rare for this type of compounds.
Keywords: Circular dichroism; Fagaceae; Oak-leaves; Proanthocyanidin glycosides; Quercus ilex; ROESY

A novel dimeric proanthocyanidin 3-O-glucoside from Quercus ilex L. (Fagaceae) - Karioti, A.; Bilia, A. R.; Skaltsa, H. (PLANTA MEDICA, 2007)
ity at room temperature in order to deactivate any enzymes and avoid polymerizations and oxidations. Final extraction was carried out using MeOH and MeOH/H2O 8/2. A fast fractionation of the residue was done using VLC over silica gel followed by repeated cc over Sephadex LH-60 and Sephadex LH-20. Fractionations were monitored with HPLC-DAD-MS. The structures of the isolated compounds were established by means of 1D & 2D NMR.
Keywords: Circular dichroism; Fagaceae; Oak-leaves; Proanthocyanidin glycosides; Quercus ilex; ROESY

Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo (The Journal of Organic Chemistry, 2004)
The nonempirical assignment of the absolute configuration of (+)-diplopyrone, the main phytotoxin of Diplodia mutila, i.e., an endophytic fungus, widespread in Sardinian oak forests, and considered one of the main causes of cork oak decline, has been approached by two different methods:? (a) the exciton analysis of the circular dichroism (CD) spectrum and (b) the ab initio calculation of the optical rotatory power. Both methods indicate that (+)-diplopyrone is 6-[(1S)-1-hydroxyethyl]-2,4a(S),6(R),8a(S)-tetrahydropyrano[3,2-b]pyran-2-one, so the stereostructure of this important biomolecule is safely determined for the first time. A comparison of advantages and limitations of the two methods of analysis is also presented.
From Duplicate 2 (Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo)
Keywords: absolute configuration; Circular dichroism; DeVoe method; diplopyrone (voyant); Mitosporic Fungi; Mitosporic Fungi: pathogenicity; Models; Molecular; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Optical rotation; Plant Diseases; Plant Diseases: microbiology; Pyrones; Pyrones: chemistry; Stereoisomerism